Diphtheria remains a threat to health in the developing world: an overview - Ana Luíza Mattos-Guaraldi; Lílian Oliveira Moreira; Paulo Vieira Damasco; Raphael Hirata Júnior (Memorias do Instituto Oswaldo Cruz, 2003)
Changes in the epidemiology of diphtheria are occurring worldwide. A large proportion of adults in many industrialized and developing countries are now susceptible to diphtheria. Vaccine-induced immunity wanes over time unless periodic booster is given or exposure to toxigenic Corynebacterium diphtheriae occurs. Immunity gap in adults coupled with large numbers of susceptible children creates the potential for new extensive epidemics. Epidemic emergencies may not be long in coming in countries experiencing rapid industrialization or undergoing sociopolitical instability where many of the factors thought to be important in producing epidemic such as mass population movements and difficult hygienic and economic conditions are present. The continuous circulation of toxigenic C. diphtheriae emphasizes the need to be aware of epidemiological features, clinical signs, and symptoms of diphtheria in vaccine era so that cases can be promptly diagnosed and treated, and further public health measures can be taken to contain this serious disease. This overview focused on worldwide data obtained from diphtheria with particular emphasis to main factors leading to recent epidemics, new clinical forms of C. diphtheriae infections, expression of virulence factors, other than toxin production, control strategies, and laboratory diagnosis procedures.